NEGLECT OF CONSTITUTIONAL RIGHTS FROM THE PERSPECTIVE OF JUSTICE - Wahab, Oki Hajiansyah (Jurnal IUS, 2013)
The constitution has clearly provided legal protection toward rights of citizen. Constitutionalism regime contains the idea of power restriction and secures civil rights through constitution. Nevertheless, some places in which agrarian conflicts occur, the ignorance of civil rights seem to be prominent. People living in the forest area of register 45 Mesuji Lampung is the picture of people who, for more than twelve years, are missing their constitutional rights. Local government does not recognize them as resident just because they occupy forest area which its management is delegated to private party. The critical legal studies perspective is constantly examining legal performance with the authority behind the law and the power within a community. Critical legal theory is focusing on the importance of a legal study which not only criticizes the substance of rule but also takes the whole aspect of social life and law into account. Â Keywords: Agrarian Conflict, Ignorance, Constitutional Rights, Citizen.